Bananas, or bananas - what other options? - Greenidge, Carl B. (Technical Centre for Agricultural and Rural Cooperation, 1994)
Carl Greenidge, a well-known Caribbean economist, is currently Deputy Secretary General of the General Secretariat of the ACP Group of States. He has worked in the Caribbean, Africa and the UK. As one of the longest serving Ministers of Finance in...